Marijuana Use from Middle to High School: Co-occurring Problem Behaviors, Teacher-Rated Academic Skills and Sixth-Grade Predictors. - Ehrenreich, Heidi; Nahapetyan, Lusine; Orpinas, Pamela; Song, Xiao (Journal of Youth & Adolescence, 2015)
Rising marijuana use and its lowered perceived risk among adolescents highlight the importance of examining patterns of marijuana use over time. This study identified trajectories of marijuana use among adolescents followed from middle through high school, characterized these by co-occurring problem behaviors and teacher-rated academic skills (study skills, attention problems, and learning problems), and tested sixth-grade predictors of trajectory membership. The sample consisted of a randomly-selected cohort of 619 students assessed annually from sixth to twelfth grade. Using group-based modeling, we identified four trajectories of marijuana use: Abstainer (65.6 %), Sporadic (13.9 %), Experimental (11.5 %), and Increasing (9.0 %). Compared to Abstainers, students in the Sporadic, Experimental and Increasing trajectories reported significantly more co-occurring problem behaviors of alcohol use, cigarette smoking, and physical aggression. Sporadic and Experimental users reported significantly less smoking and physical aggression, but not alcohol use, than Increasing users. Teachers consistently rated Abstainers as having better study skills and less attention and learning problems than the three marijuana use groups. Compared to Abstainers, the odds of dropping out of high school was at least 2.7 times higher for students in the marijuana use trajectories. Dropout rates did not vary significantly between marijuana use groups. In sixth grade, being male, cigarette smoking, physical aggression and attention problems increased the odds of being in the marijuana use trajectories. Multiple indicators-student self-reports, teacher ratings and high school dropout records-showed that marijuana was not an isolated or benign event in the life of adolescents but part of an overall problem behavior syndrome.